ANALISIS SISTEM INFORMASI PERSEDIAAN PRODUK BERBASIS WEB (Studi Kasus Pada PT. Firman Ardy Cabang Kota Malang) - Sal Sabila Rahmadhani; Moh. Amin; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
This study aims to determine the application of a web-based product inventory information system in a trading company at PT. Firman Ardy Malang City branch. This type of research uses a qualitative method with a descriptive approach. The data obtained from the results of interviews with research subjects. The technique used to analyze web-based product inventory data is by collecting data and then processing it so that conclusions can be drawn. The result of this research is that a web-based system has many benefits both for the owner, and for employees and its easy implementation.Keywords: Information System, Inventory, Web